Diverse myopathological features in the congenital myasthenia syndrome with GFPT1 mutation. Issue 2 (3rd January 2022) - Jiang, Kaiyan; Zheng, Yilei; Lin, Jing; Wu, Xiaorong; Yu, Yanyan; Zhu, Min; Fang, Xin; Zhou, Meihong; Li, Xiaobing; Hong, Daojun
Abstract: Introduction: Mutations in the GFPT1 gene are associated with a particular subtype of congenital myasthenia syndrome (CMS) called limb‐girdle myasthenia with tubular aggregates. However, not all patients show tubular aggregates in muscle biopsy, suggesting the diversity of myopathology should be further investigated. Methods: In this study, we reported two unrelated patients clinically characterized by easy fatigability, limb‐girdle muscle weakness, positive decrements of repetitive stimulation, and response to pyridostigmine. The routine examinations of myopathology were conducted. The causative gene was explored by whole‐exome screening. In addition, we summarized all GFPT1 ‐related CMS patients with muscle biopsy in the literature. Results: Pathogenic biallelic GFPT1 mutations were identified in the two patients. In patient one, muscle biopsy indicated vacuolar myopathic changes and atypical pathological changes of myofibrillar myopathy characterized by desmin deposits, Z‐disc disorganization, and electronic dense granulofilamentous aggregation. In patient two, muscle biopsy showed typical myopathy with tubular aggregates. Among the 51 reported GFPT1 ‐related CMS patients with muscle biopsy, most of them showed tubular aggregates myopathy, while rimmed vacuolar myopathy, autophagic vacuolar myopathy, mitochondria‐like myopathy, neurogenic myopathy, and unspecific myopathic changes were also observed in some patients. These extra‐synaptic pathological changes might be associated with GFPT1‐deficiency hypoglycosylation and altered function of muscle‐specific glycoproteins, as well as partly responsible for the permanent muscle weakness and resistance to acetylcholinesterase inhibitor therapy. Conclusions: Most patients with GFPT1 ‐related CMS had tubular aggregates in the muscle biopsy, but some patients could show great diversities of the pathological change. The myopathological findings might be a biomarker to predict the prognosis of the disease.